Human factors in the emergency department: Is physician perception of time to intubation and desaturation rate accurate?. (13th April 2016) - Cemalovic, Nail; Scoccimarro, Anthony; Arslan, Albert; Fraser, Robert; Kanter, Marc; Caputo, Nicholas
Abstract: Objective: The main objective of the present study was to examine the perceived versus actual time to intubation (TTI) as an indication to help determine the situational awareness of Emergency Physicians during rapid sequence intubation and, additionally, to determine the physician's perception of desaturation events. Methods: A timed, observation prospective cohort study was conducted. A post‐intubation survey was administered to the intubating physician. Each step of the procedure was timed by an observer in order to determine actual TTI. The number of desaturation events was also recorded. Results: One hundred individual intubations were included. The provider perceived TTI was significantly different and underestimated when compared with the actual TTI (23 s, 95% confidence interval (CI) 20.4–25.49 vs 45.5 s, 95% CI 40.2–50.7, P < 0.001, respectively). Pearson correlation coefficient of perceived TTI to actual TTI was r 2 = 0.39 (95% CI 0.21–0.54, P < 0.001). The provider perceived desaturation rate was also significantly different from actual desaturation rate (13, 95% CI 3–12 vs 23, 95% CI 13–29, P = 0.05, respectively). The overall time to desaturation was 65.1 s. Conclusions: Our findings have shown that provider's perception of TTI occurs sooner than actually observed. Also, the providers were less aware of desaturation during the procedure.